141k views
1 vote
Equation is x"-4x=0, general solution is x(t) = C1e^-2t+C2e^2t, initial condition is x(0) = 1, x'(0)=0

User Sadiel
by
5.2k points

1 Answer

3 votes

Answer:


x(t)=(1)/(2)e^(-2t)+(1)/(2)e^(2t)

Explanation:

The given differential equation is
x''-4x=0

The characteristics equation is given by


r^2-4=0\\\\r^2=4\\\\r=\pm2

Therefore, the solution of the DE is given by


x(t)=c_1e^(-2t)+c_2e^(2t)

On differentiating, we get


x'(t)=-2c_1e^(-2t)+2c_2e^(2t)

Apply the initial conditions

x(0)=1


1=c_1e^(0)+c_2e^(0)\\\\c_1+c_2=1...(i)

Second condition is x'(0)=0


0=-2c_1e^(0)+2c_2e^(0)\\\\-2c_1+2c_2=0\\\\c_1-c_2=0...(ii)

Add (i) and (ii)


2c_1=1\\\\c_1=(1)/(2)

Substituting this value in (ii)


(1)/(2)-c_2=0\\\\c_2=(1)/(2)

Hence, the solution of the DE is


x(t)=(1)/(2)e^(-2t)+(1)/(2)e^(2t)

User AJ Richardson
by
5.7k points